Prognostic impact of lymphovascular invasion in node-negative gastric cancer: a retrospective cohort study - Abdullah Ibrahim Alangari; Sojung Kim; Han Hong Lee; Kyo Young Song; Hoseok Seo (World Journal of Surgical Oncology)
Abstract Background Lymphovascular invasion (LVI) has been identified as a prognostic factor in various cancers, but its significance in node-negative gastric cancer remains unclear. Gastric cancer prognosis is notably affected by lymph node metastasis, with LVI potentially indicating metastatic spread. Methods A retrospective review was conducted on 5,699 patients who underwent curative radical gastrectomy for gastric cancer between 1989 and 2018. The median follow-up duration was 62 months (0–362 months). Overall, disease-specific, and disease-free survival were compared based on LVI status and stratified by T stage. Additionally, patients with stage IIA or T2N0 were further evaluated to clarify the clinical significance of LVI in the T2N0 group. Results The T2N0 LVI-positive group exhibited significantly poor prognosis than those in the T2N0 LVI-negative group, with no significant differences observed on comparing the T2N0 LVI-positive group with the T2N1 LVI-negative or LVI-positive groups. Furthermore, although the T2N0 LVI-negative group demonstrated better prognosis compared to the IIA group, the T2N0 LVI-positive group exhibited worse survival. In addition, LVI positivity was an independent risk factor for overall survival in T2N0 patients. Conclusions LVI in node-negative gastric cancer has clinical significance as a prognostic indicator, indicating an increased risk of disease recurrence and poor survival especially in T2 cohort. This indicates an increased likelihood of lymph node involvement and may influence treatment decisions and follow-up strategies.